2009
DOI: 10.1590/s0104-42302009000300029
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre o padrão de atividade física materna, ganho ponderal gestacional e peso ao nascer em uma coorte de 118 gestantes no município de Campina Grande, Nordeste do Brasil

Abstract: All the pregnant women were sedentary in the third trimester and a significant association between physical activity pattern and gestational weight gain was found in the second trimester, but there was no association between this pattern and birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
4
1
4
Order By: Relevance
“…However, we found that BMI was inversely related with GWG in overweight and obese women, which is consistent with previous findings. 18,19 We also report that there was no relationship between physical activity and GWG. Despite meta-analysis reporting that antenatal exercise interventions are effective in limiting GWG in the overweight and obese population, 8 previous literature also suggests that only vigorous physical activity for leisure is associated with less GWG.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, we found that BMI was inversely related with GWG in overweight and obese women, which is consistent with previous findings. 18,19 We also report that there was no relationship between physical activity and GWG. Despite meta-analysis reporting that antenatal exercise interventions are effective in limiting GWG in the overweight and obese population, 8 previous literature also suggests that only vigorous physical activity for leisure is associated with less GWG.…”
Section: Discussionmentioning
confidence: 85%
“…17 In addition, there is limited information describing cross-sectional comparisons or changes in physical activity from pregnancy to postpartum in women of different GWG categories with an inverse correlation previously reported between GWG and physical activity. 18,19 A comprehensive evaluation of physical activity patterns across pregnancy and the postpartum period is warranted to aid in identification of appropriate time points in which to target future interventions to prevent both excessive gestational weight gain and postpartum weight retention. This is particularly relevant in overweight and obese women given the additional adverse maternal, fetal and child outcomes associated with increased adiposity during and following pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Tavares at al. 22 studied the effects of physical activity on gestational weight gain and birth weight of pregnant women in Campina Grande, northeast of Brazil, and found that all the pregnant women were sedentary in the third trimester and that there was a significant association between physical activity patterns and gestational weight gain in the second trimester but that there was no association between this pattern and birth weight. Balen et al 23 reported on a murine model of protein restriction in pregnant and non-pregnant rats and concluded that protein restriction in pregnancy modified maternal metabolism, altering lipid synthesis in the liver and hormonal profiles and decreasing the placental and fetal masses.…”
Section: Methodsmentioning
confidence: 99%
“…Já entre o peso no nono mês e a intensidade da dor nesse período, houve uma correlação moderada e significativa 22 . No nosso estudo, as gestantes avaliadas apresentaram valores de IMC dentro do recomendado para o trimestre gestacional 13 , visto que um ganho de peso corporal de até 16 kg é considerado adequado, expressando o crescimento fetal, expansão de tecidos maternos, placenta, útero e mamas, e formação do líquido amniótico 22,24 . Além disso, tomou-se o cuidado de selecionar um instrumento de avaliação da qualidade de vida ("Medical Outcomes Study-36") que abrangesse as dimensões de capacidade funcional e aspectos físicos, com perguntas relacionadas ao impacto do trabalho/ocupação na vida da gestante.…”
Section: Artigo Originalunclassified